Gut Microbiota as a Biomarker in Colorectal Cancer (CIPEEX, 2025)
Introduction: In the past fiew years, the understanding of the role of the gut microbiota in colorectal cancer (CRC) has evolved significantly, standing out not only as a risk factor for carcinogenesis but also as a crucial element for patient prognosis and treatment response1,2,3,4. In this context, recent studies have demonstrated that specific bacterial signatures can act as biomarkers of clinical outcomes, in addition to directly influencing mechanisms of tumor resistance1,2,3,4. Thus, the objective of these investigations was to deepen the relationship between dysbiosis, clinical outcomes, and therapeutic efficacy in patients with colorectal cancer, in treatment settings involving surgery, chemotherapy, radiotherapy, and immunotherapy 1,2,3,4. Objective: To critically evaluate the current scientific literature in order to verify the association between gut microbiota and colorectal neoplasia and its influence on disease prognosis. Methodology: This is an integrative literature review, in which scientific publications were searched in the PubMed database. The English descriptors “Colorectal neoplasms,” “Dysbiosis,” “Prognosis,” and “Gut microbiota” were used, with “AND” as the only Boolean operator. Filters were applied for articles published in the last 5 years and with free full-text availability. This search resulted in 20 articles, from which 4 were selected for the sample that composes this integrative review. Results: In a prospective study, the analysis of fecal samples collected before surgery identified that the presence of Prevotella and three other microorganisms represented independent markers of worse prognosis, associated with higher risk of recurrence and reduced survival1. This work reinforces the idea that the preoperative microbiota may serve as a predictive tool complementary to traditional clinical assessment1. In another approach, patients undergoing neoadjuvant chemoradiotherapy had their fecal samples evaluated for microbial composition, short-chain fatty acids, and polyamines, showing that both diversity and bacterial metabolites influenced tumor response, indicating a possible metabolic–microbial role in radiosensitivity2. Complementarily, an innovative proposal emerged with the creation of a microbiota ecological score, based on network topology analysis of bacterial interactions, which consistently predicted outcomes in patients undergoing immunotherapy3. This type of approach expands the view of the microbiota as a simple list of species, proposing that the interaction between microorganisms is decisive for clinical and prognostic impact3. On the other hand, in a mechanistic study, it was observed that Fusobacterium nucleatum, already established as a pathogen associated with CRC, can confer chemotherapy resistance by inhibiting cellular pyroptosis through the Hippo pathway, a mechanism that may help explain why certain patients experience therapeutic failure even under standard protocols4. Conclusion: Evidence indicates that the gut microbiota plays a multifaceted role in colorectal neoplasia, influencing everything from the risk of recurrence after surgery, to the modulation of response to chemoradiotherapy, to the efficacy of immunotherapy and conventional chemotherapy1,2,3,4. Thus, the incorporation of microbiota analyses into future clinical practice may allow not only more accurate risk stratification but also the development of personalized therapeutic strategies.
Keywords: colorectal neoplasms; dysbiosis; prognosis; gut microbiota